Jalan Panjang Penyelesaian Konflik Kasus Lumpur Lapindo - Anis Farida (Jurnal Ilmu Sosial dan Ilmu Politik, 2013)
This study aims to understand the map of conflict and the evolving dynamics of Lapindo mudflow case settlement. The study was conducted in two villages, namely Siring and Renokenongo, Porong subdistrict, Sidoarjo, EastJava, using a qualitative approach. Data was collected throughin-depth interviews, observation, documentation and focus group discussion. The results showed that the conflict can be divided into vertical and horizontal conflicts. In the vertical conflict, communities faced government and Lapindo Brantas. While horizontal conflicts, it showed a layer conflicts, consisting of the conflict between family members, neighbors, RT/RW, villagers, and between Lapindo mudflow victims vs nonvictims residents. Simplification of Lapindo conflict management based on there placement of material aspects, have potentially to create a new problems in the future.